2021
DOI: 10.3390/ijms22052563
|View full text |Cite
|
Sign up to set email alerts
|

A Commonly Used Biocide 2-N-octyl-4-isothiazolin-3-oneInduces Blood–Brain Barrier Dysfunction via Cellular Thiol Modification and Mitochondrial Damage

Abstract: Isothiazolinone (IT) biocides are potent antibacterial substances commonly used as preservatives or disinfectants, and 2-n-Octyl-4-isothiazolin-3-one (OIT; octhilinone) is a common IT biocide that is present in leather products, glue, paints, and cleaning products. Although humans are exposed to OIT through personal and industrial use, the potentially deleterious effects of OIT on human health are still unknown. To investigate the effects of OIT on the vascular system, which is continuously exposed to xenobiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Furthermore, the potential harmful effects of OIT on human health are still not well elucidated. Kim et al 4 showed in their in vitro study that OIT induced blood brain barrier dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the potential harmful effects of OIT on human health are still not well elucidated. Kim et al 4 showed in their in vitro study that OIT induced blood brain barrier dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, IsoB exhibited a potent effect against mitochondrial integrity, notably causing a significant decrease in membrane potential (ΔΨm) after 48 h of incubation and an increase in superoxide levels after 24 h of incubation in Huh7 cells. In other studies, isothiazolone derivatives have similarly demonstrated effects of inducing mitochondrial dysfunction in the brain [ 46 , 47 ], bronchial cells [ 48 ], and primary vascular muscle cells [ 49 ], underscoring their potential role in cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…TJ proteins are essential for proper BBB function. However, when the TJ protein is damaged by factors such as ischemic stress and xenobiotics, permeability increases and the brain may not be adequately protected [ 67 , 68 , 69 , 70 ]. We used sub-lethal ischemic stimuli of 6 h of OGD that did not significantly reduce cell viability [ 26 ], and then observed the degradation of ZO-1 and claudin-5 with a confocal microscope.…”
Section: Discussionmentioning
confidence: 99%